Les Deux Angleterres et le Continent. Anglophone Sociology as the Guardian of Old European Semantics - Steffen Roth (Journal of Sociocybernetics, 2011)
Despite its influence in Central European sociology, N. Luhmann's Social Systems theory remains a marginal branch of international sociology. In this paper, the theory questions the reasons for its own marginality in general and for its marginality in the Anglophone centers of sociology in particular, with the latter still being a surprise against the background of the theory's cybernetic roots in the US. The theory arrives at the conclusion that, while Europe, or `the continent', is still perceived as old compared with the Anglophone new world(s), it still is Anglophone sociology that preserves `Old European' semantics. Sociology in continental `Old Europe', however, seems to have a chance of slowly being acquainted with a new, post-enlightenment mindset focused on semantics and communication rather than on humans and action.
Keywords: 330; Luhmann; Sociology; Communication; Social Systems Theory